Jatuhnya Kota Konstantinopel (1453) oleh Turki Utsmani Kepemimpinan Sultan Muhammad Al-Fatih - Saputra, Mochammad Ronaldy Aji (Qurthuba: The Journal of History and Islamic Civilization, 2024)
The city of Constantinople was the capital of the Eastern Roman Empire (Byzantium). The specialty of this city is its strategic location so it has an important role as a trade intermediary for kingdoms in Europe and Asia. Geopolitically and strategically, Sultan Muhammad Al-Fatih's position is very profitable. This advantage allowed the Sultan to build his navy in 1451 and strengthen the defense of the Bosporus South region with the construction of the Rumeli Hisari Fortress in 1452. The conquest of the city of Constantinople took place from April 6 to May 29, 1453. This conquest was a battle of weapons and strategy. The impact of the conquest of the city of Constantinople was to confirm the status of the Ottoman Empire as a major power in Southeastern and Eastern Europe, change the map of power in the Mediterranean region, end the Middle Ages in Europe, and give birth to the Age of Renaissance and the birth of ocean exploration.